ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, RASIO AKTIVITAS, DAN RASIO PROFITABILITAS PADA PT PIKKO LAND DEVELOPMENT Tbk PERIODE 2013-2022 - Dharmawan, Wahyu; Syakhrial (Journal of Research and Publication Innovation, 2024)
This study aims to analyze financial performance based on liquidity ratios, activity ratios, and profitability ratios at PT Pikko Land Development Tbk for the period 2013-2022. The method used is quantitative. The population used in this study were all financial statements of PT Pikko Land Development Tbk for the period 2013-2022, of which the samples in this study were balance sheet and profit and loss statements for the period 2013-2022. The data analysis used in this study is ratio analysis with a comparison of industry standard financial ratios according to Kasmir (2019). The results showed that the liquidity ratio (current ratio) was categorized as “good” because the value was 346%, meaning above 200% of the industry average standard, this is because the company is able to pay off current liabilities using its current assets. Based on the activity ratio (total asset turnover), it is categorized as “not good” because its value is 0.14 times, which means below 2 times the industry average standard, this is because the company is unable to maximize the use of assets effectively and efficiently. Based on the profitability ratio (return on assets) is categorized as “not good” because its value is 4%, which means below 30% of the industry average standard, this is because the company does not maximize the assets invested to generate profits or profits.